RENDERING ABBREVIATIONS AND SYMBOLS OF BIOLOGICAL TEXTS FROM ENGLISH INTO UZBEK - Komilova, Maftuna Mahmud qizi (INTERNATIONAL CONFERENCES, 2023)
This paper discusses some effective ways of translating scientific data in the form of abbreviations and symbols of biological texts from English language into Uzbek. It provides a number of examples for rendering such data and gives clear practical recommendations for future translators.